Determination of optimum shape of pinned parabolic arch structures under uniformly distributed loads: a blend of cost and functionality - Victor Mmerichukwu Mbachu; Victor Odinaka Okonkwo (Journal of Construction Project Management and Innovation)
The construction industries are faced with multiple decisions that borders around functionality and cost. Such decision is made when considering the geometry of arches. In this work, hinged arch structures were examined under uniformly distributed static loads, and an attempt to find the best arch height for any given arch span was made. An optimum orientation of the elements of two-hinged parabolic arch structures was selected based on the manufacturing cost, which was adjudged by the volume of concrete consumed. Stress – strain analysis was used to compute for the volume of the arch, while the usefulness or benefit of the arch was taken as the ratio of the frames’ cross sectional area to their perimeter. Graphs of the cost-benefit ratio against arch height f were plotted for different values of arch span and the values of arch height corresponding to minima cost/benefit were obtained. These values were found to be independent of the ratio of the load to the product of arch thickness and grade of arch material (w/σb). A table showing the values of economic arch height for different values of arch span was presented and a reliable model (polynomial equation) was developed.